Analisis Pemanfaatan Sampah Kulit Manggis di Desa Pangradin Kecamatan Jasinga Kabupaten Bogor - Jamaludin, Jamaludin; Alhubbufillah, Muhammad Alfi; Setiabudi, Rahmat (El-Mujtama: Jurnal Pengabdian Masyarakat, 2024)
The people of Pangradin Village, Jasinga District, have minimal knowledge of the benefits of mangosteen rind. Usually mangosteen skin is only organic waste, but actually many other benefits are produced from mangosteen rind. Community service is carried out in the village of Pangradin. The method of implementing community service is an approach method through counseling, question and answer and discussion. The results of this community service can increase people's understanding of the benefits of mangosteen rind for health. Keywords: Mangosteen Skin, Pangradin Village